ПАМФЛЕТ КАК ХУДОЖЕСТВЕННЫЙ ЖАНР. - Гезалова, Наргиз Джафар к. (Eurasian Journal of Philology Science and Education, 2015)
This article is devoted to the place of the pamphlet in theEnglish writer’s creative activity. Here the main peculiarities ofthe existing social problems are revealed by this genre. It iscommonly known that the English literary conception from theend of the XVII c. up to the beginning of the XVIII c. appealedto the potential opportunities of the given genre.